BEHAVIORAL STUDIES OF COASTAL COMMUNITIES AROUND THE THREE-COLOR CMC BEACH FROM AN ENVIRONMENTAL PERSPECTIVE - Adyatma, Sidharta; Puspita, Elzanadia; Marlina, Marlina; Norhatimah, Norhatimah; Andariani, Yogi Restu Nuri; Arifin, Alam (International Conference On Social Science Education, 2024)
Indonesia's coastal areas, where land and sea meet, are rich in natural resources that provide economic benefits such as fisheries and tourism, and support ecosystem balance. Community dependence on these resources can lead to environmental damage if not appropriately managed. This article analyzes the behavior of the Tambakrejo community at CMC Tiga Warna Beach in terms of environmental preservation through tourism and conservation. The study employs a qualitative descriptive method, incorporating interviews and observations. Results show significant community impacts on ecosystems, such as waste pollution and land clearing, threatening biodiversity. Ecotourism at CMC Tiga Warna Beach encourages active community roles in conservation, including visitor limits and mangrove planting. The interaction between community behavior, ecosystems, and local culture plays a role in environmental preservation. Community participation and local policies have been shown to support coastal sustainability. This emphasizes the need for community-based approaches to minimize negative impacts and enhance the benefits of ecotourism.